Electrophysiological and histological characterization of atrial scarring in a model of isolated atrial myocardial infarction - Amorós-Figueras, Gerard; Casabella-Ramon, Sergi; Company-Se, Georgina; Arzamendi, Dabit; Jorge, Esther; Garcia-Osuna, Alvaro; Macías, Yolanda; Sánchez-Quintana, Damián; Rosell-Ferrer, Javier; Guerra, José M.; Cinca, Juan (Frontiers in Physiology, 2023)
Background: The diagnosis of atrial infarction is often masked by its frequent association with ventricular infarction and this accounts for the limited knowledge on the intrinsic electrophysiological and structural consequences of atrial infarction. Objective: This study aimed at analyzing the alterations in the ECG, local atrial electrograms and multifrequency impedance in a closed-chest model of isolated atrial infarction. Methods: Seven anesthetized pigs were submitted to transcatheter occlusion of atrial coronary branches arising from the left coronary circumflex artery while recording the ECG. Six weeks later the animals were anesthetized and we performed an atrial voltage mapping and multifrequency impedance recordings. The hearts were thereafter extracted for anatomopathological study. Two additional pigs not submitted to atrial branch occlusion were used as controls. Results: Selective occlusion of the atrial branches induced areas of healed infarction in the left atrium in 6 of the 7 cases. The ECG showed prolongation of the P-wave duration (lead I: 66±8ms at baseline vs. 81±11ms at 6 weeks, p <0.05). Deviation of the PR segment was not consistently found. Endocardial mapping of the left atrium showed low-voltage of bipolar electrograms (0.2±0.1mV vs 1.9±1.5mV vs, p <0.01) and reduced multi-frequency impedance (Phase angle at 300 kHz: from -17.1±5.0° to -8.9±2.6°, p<0.01) in areas affected by the infarction. Conclusion: Atrial infarction induces widening and flattening of the P wave. Endocardial electrical and impedance mapping can recognize atrial fibrosis and may have potential applicability on the study of atrial arrhythmia mechanisms.